1998
DOI: 10.1002/(sici)1521-3773(19981116)37:21<2960::aid-anie2960>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Gas Separation with Polymer Membranes

Abstract: Gas-selective polymer membranes have long been used in industrial applications. Studies of polymers with well-defined flexible phenyl ether segments such as 1 should contribute to the understanding of the selection mechanism and thus ultimately lead to the synthesis of optimized membrane materials. Various different bridging groups X were used in the studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(51 citation statements)
references
References 21 publications
1
48
0
2
Order By: Relevance
“…For example, commercial pervaporation systems for dehydration of alcohol were introduced in Germany by GFT (a small engineering company) in the 1980s (Baker, 2004). A plant separating air into its constituent gases and producing pure nitrogen at nearly 24 t h −1 in Belgium by Praxair Co. began operation in 1996 (Maier, 1998). Since the development of ultrafiltration as a viable industrial process in the 1960s, there have been literally thousands of different ultrafiltration membranes sold commercially.…”
Section: Introductionmentioning
confidence: 99%
“…For example, commercial pervaporation systems for dehydration of alcohol were introduced in Germany by GFT (a small engineering company) in the 1980s (Baker, 2004). A plant separating air into its constituent gases and producing pure nitrogen at nearly 24 t h −1 in Belgium by Praxair Co. began operation in 1996 (Maier, 1998). Since the development of ultrafiltration as a viable industrial process in the 1960s, there have been literally thousands of different ultrafiltration membranes sold commercially.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of the equilibrated PEBAX/KET models at different additive compositions (30 wt %, 50 wt %, 70 wt %) was also tested by comparing simulated permeability coefficients of five gas molecules, H 2 , O 2 , N 2 , CH 4 and CO 2 and water vapor with experimental data already available from Gugliuzza et al, [10][11][12]. Table 3 summarizes the theoretical transport parameters and the available experimental values for PEBAX/KET systems in different compositions.…”
Section: Gas and Vapor Permeabilitymentioning
confidence: 99%
“…However, there is a key technical challenge to be met: That of achieving higher permeability and higher selectivity [2]. Special attention has been paid to the use of membranes in a solubility-selective mode in recent years, obtaining preferential permeation through the membranes of more soluble gaseous species [3,4]. Polymers containing poly(ethylene oxide) units have an interesting CO 2 /N 2 selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric membranes, as opposed to inorganic ones, are widely used in gas and liquid separation due to their advantages such as ease of preparation, flexibility and other desirable properties (Maier, 1998;George and Thomas, 2001;Freeman and Pinnau, 1999). Robeson (1991) revealed that, even though these advantages exist, polymeric membranes still suffer from a trade-off between gas permeability and selectivity.…”
Section: Introductionmentioning
confidence: 99%